Alumni Assistance to Increase Personal Potential Phase II in Efforts to Reduce Stunting Incidents with Toddler Massage - Ririn Indriani; Susanti Pratamaningtyas; Eny Sendra (PT FORMOSA CENDEKIA GLOBAL, 2023)
Based on data from 2021, it is predicted that graduates from several health care majors will experience saturation by 2024, including midwifery graduates. Midwifery has a large number of graduates but this is not matched by the availability of job opportunities. This means that some graduates are forced to not work or work that is not appropriate to their field. So the Community Service team created a program entitled